PATTERNS OF CHANGE IN TECHNOLOGICAL ACCURACY OF WOODWORKING MACHINES DURING OVERHAUL PERIOD - Pylypchuk, M.I.; Taras, V.I.; Burdyak, M.R.; Zhmudyk, V.T. (Forestry, Forest, Paper and Woodworking Industry, 2021)
The patterns of changes in the technological accuracy of the machine during the overhaul period in the form of a polynomial dependence have been identified, which makes it possible to determine the time and number of adjustments to the machine to ensure its operating capacity according to the criterion of technological accuracy. On the basis of the statistical modeling method, a simulation model-program "ModDynToch" was developed for identifying changes in the technological accuracy of the machine tool with the determination of the time between failures and the required number of machine adjustments during the overhaul period. Based on the results of modeling changes in the technological accuracy of a number of machines for sawing and milling wood, it was found that in order to ensure a working capacity during the overhaul period, each machine requires three adjustments to be made at a certain interval. Based on the analysis of the results of modeling changes in the technological accuracy of machines for sawing and milling wood, it was found that the shortest period of operation for band saw machines is up to 190 hours, for circular saw machines – up to 480 hours, and for milling machines – up to 840 hours. The results of the statistical modeling of the pattern of changes in the technological accuracy of machines during the overhaul period of operation are correlated with operational data with an accuracy of up to 7%, which confirms the reliability of the modeling results.